Tuberculine test in infants and children who have contact to sputum positive adult pulmonary tuberculosis patients - Khainir Akbar; Ridwan M. Daulay; Helmi Lubis; Zakaria Siregar; Gabriel Panggabean; Nuraida Nuraida (Indonesian Pediatric Society, 1999)
This study aimed to determine the pattern of pulmonary tuberculosisinfection in infants and children who had household contact to adtult tuberculosis patients with sputum positive for acid-fast bacilli (AFB). Tuberculine (Mantoux) test was performed in 270 such infants or children. The results showed that tuberculine test positivity in household contact group of adult tuberculosis patients with positive AFB sputum were significantly different from patients with negative AFB sputum for the age groups 0-18, 0-14, 0-4, 5-9, 10-14 years but not for 15-18 age group. There were no significant difference in positivity of tuberculine test result according to gender or BCG vaccination status, but there was significant difference between children who slept in the same bed room with the source case and those who did not. Semi-quantitative bacteriological status of the sputum (AFB +, or++ or+++) did not affect positivity of tuberculine test result. We conclude that infants and children with household contact to sputum positive adult pulmonary tubercula is patients are at high risk for developing tuberculosis infection particularly those who sleep in the samebed room with the source case.